2020
DOI: 10.1038/s41598-020-78621-7
|View full text |Cite
|
Sign up to set email alerts
|

Value of peak strain dispersion in discovering left ventricular dysfunction in diabetes mellitus

Abstract: Cardiovascular disease is one of the main causes of death in diabetes mellitus (DM) patients. The aim of the current study was to explore the value of peak strain dispersion (PSD) for discovering early-stage left ventricular (LV) dysfunction in type 2 diabetes mellitus (T2DM) patients. One hundred and one T2DM patients and sixty healthy subjects were selected for this study. T2DM patients were further divided into controlled blood glucose (HbA1c < 7%, n = 46) and uncontrolled blood glucose (HbA1c ≥ 7%, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
1
14
0
2
Order By: Relevance
“…The stimulation mode influenced not only electrical but also mechanical synchrony, as evidenced by the peak systolic dispersion (PSD) measurements obtained using 2D STE. PSD adequately reflects the degree of mechanical dyssynchrony accompanying electrotherapy [ 16 ] and is used to assess left ventricular dysfunction in other pathologies as well [ 17 , 18 ]. Our PSD results are consistent with our findings for QRSd.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation mode influenced not only electrical but also mechanical synchrony, as evidenced by the peak systolic dispersion (PSD) measurements obtained using 2D STE. PSD adequately reflects the degree of mechanical dyssynchrony accompanying electrotherapy [ 16 ] and is used to assess left ventricular dysfunction in other pathologies as well [ 17 , 18 ]. Our PSD results are consistent with our findings for QRSd.…”
Section: Discussionmentioning
confidence: 99%
“…PSD is the standard deviation of the peak time of the longitudinal strain in 17 segments of the left ventricle. 15 There was a statistically significantly increase in PSD in the mild-to-moderate and severe groups compared to the control group, indicating that the dispersion of myocardial mechanical motion is increased, that is, myocardial systolic synchronization is worse. 16 It has been suggested that the deposition of SLE-associated immune complexes in the cardiovascular system may lead to degeneration of cardiomyocytes and myocardial sympathetic nerves, which directly leads to the damage of the normal function of cardiomyocytes and the dysfunction of nerve fibers in the myocardial layer; this, in turn, has a serious impact on myocardial synchronous movement.…”
Section: Discussionmentioning
confidence: 89%
“…PSD is the standard deviation of the peak time of the longitudinal strain in 17 segments of the left ventricle 15 . There was a statistically significantly increase in PSD in the mild‐to‐moderate and severe groups compared to the control group, indicating that the dispersion of myocardial mechanical motion is increased, that is, myocardial systolic synchronization is worse 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Em um estudo, 25 o grupo controle era constituído de hipertensos sem diabetes. Alguns Diferentes avaliações também foram estudadas nessa população, como: índice de trabalho miocárdico, 26,27 torsão miocárdica por speckle tracking, 28 disfunção sistólica do ventrículo direito por speckle tracking, 29 função cardíaca durante atividade física e capacidade ao exercício, 24,30,31 valor de dispersão entre picos sistólicos do strain, 32 efeito da frequência cardíaca, 7 função cardíaca durante ecocardiografia por estresse com dobutamina, 33 variabilidade da frequência cardíaca, 23 progressão da disfunção diastólica 34 e análise multilayer por speckle tracking. 17,23 As características ecocardiográficas de interesse para esta revisão estão apresentadas nas tabelas 3 e 4.…”
Section: Resultsunclassified
“…Em relação especificamente ao controle glicêmico, Lind et al, em estudo com 20.985 indivíduos com DM1, concluíram que, mesmo após o ajuste de outros fatores de risco cardiovascular, o risco de insuficiência cardíaca ainda foi quatro vezes maior em pacientes com mau controle glicêmico comparados aos com ótimo controle glicêmico, e cada 1% de aumento na HbA1c correspondeu a um aumento de 30% no risco de desenvolver insuficiência cardíaca. 40 Li et al exploraram a relação entre controle glicêmico e disfunção ventricular esquerda em indivíduos com DM2 por meio do valor de HbA1c; 32 não houve diferença na FEVE, entretanto, havia diferença entre o índice de massa ventricular e a velocidade de onda E mitral entre os grupos com DM versus controle, sendo maior a diferença no grupo com pior controle glicêmico. Além disso, não se observou diferença do SGL entre o grupo com bom controle glicêmico e o grupo controle.…”
Section: Artigo De Revisão Sistemáticaunclassified